Combining POLDER-3 satellite observations and WRF-Chem numerical simulations to derive biomass burning aerosol properties over the southeast Atlantic region - Siméon, Alexandre; Waquet, Fabien; Péré, Jean-Christophe; Ducos, Fabrice; Thieuleux, François; Peers, Fanny; Turquety, Solène; Chiapello, Isabelle (Atmospheric chemistry and physics, 2021)
Aerosol absorption is a key property to assess the radiative impacts of aerosols on climate at both global and regional scales. The aerosol physico-chemical and optical properties remain not sufficiently constrained in climate models, with difficulties to properly represent both the aerosol load and their absorption properties in clear and cloudy scenes, especially for absorbing biomass burning aerosols (BBA). In this study we focus on biomass burning (BB) particle plumes transported above clouds over the southeast Atlantic (SEA) region off the southwest coast of Africa, in order to improve the representation of their physico-chemical and absorption properties. The methodology is based on aerosol regional numerical simulations from the WRF-Chem coupled meteorology–chemistry model combined with a detailed inventory of BB emissions and various sets of innovative aerosol remote sensing observations, both in clear and cloudy skies from the POLDER-3/PARASOL space sensor. Current literature indicates that some organic aerosol compounds (OC), called brown carbon (BrOC), primarily emitted by biomass combustion absorb the ultraviolet-blue radiation more efficiently than pure black carbon (BC). We exploit this specificity by comparing the spectral dependence of the aerosol single scattering albedo (SSA) derived from the POLDER-3 satellite observations in the 443–1020 nm wavelength range with the SSA simulated for different proportions of BC, OC and BrOC at the source level, considering the homogeneous internal mixing state of particles. These numerical simulation experiments are based on two main constraints: maintaining a realistic aerosol optical depth both in clear and above cloudy scenes and a realistic BC/OC mass ratio. Modelling experiments are presented and discussed to link the chemical composition with the absorption properties of BBA and to provide estimates of the relative proportions of black, organic and brown carbon in the African BBA plumes transported over the SEA region for July 2008. The absorbing fraction of organic aerosols in the BBA plumes, i.e. BrOC, is estimated at 2 % to 3 %. The simulated mean SSA are 0.81 (565 nm) and 0.84 (550 nm) in clear and above cloudy scenes respectively, in good agreement with those retrieved by POLDER-3 (0.85±0.05 at 565 nm in clear sky and at 550 nm above clouds) for the studied period.